Static and dynamic stability analysis of a steel-rubber isolator with rubber cores. (August 2020) - Rahnavard, Rohola; Craveiro, Helder D.; Napolitano, Rebecca
Abstract: Stability is one of the most important parameters to evaluate seismic base isolators. Previous research has illustrated the power of base isolators with single and multiple rubber cores. While that work provided a critical introduction to this innovative idea, the lateral stability of seismic steel-rubber base isolators with single and multiple rubber cores was not evaluated; thus it is the topic of the current work. The finite element method is used for modeling of the elastomeric bearing. Three methods, including reduced area formula, quasi-static, and dynamic analysis, were used. The Ogden method is used for modeling rubber material properties. The effect of the size and number of rubber cores on the stability of elastomeric bearing is also investigated. The obtained results show that the use of single and multiple rubber cores increases isolator stability due to the large critical vertical loads. Also, the results of quasi-static methods and dynamic analysis for single rubber core isolators showed that increasing the core diameter has a slight effect on stability. A comparison of the results from the quasi-static and dynamic analysis shows a good agreement, confirming that the simpler quasi-static method is effective to numerically measure the stability limit of steel-rubber base isolators.